Association of dietary intake and physical activity with hypercholesterolemia among prolanis participants - Sutrio Sutrio; Arie Nugroho; Endang Sri Wahyuni; Sefanadia Putri (AcTion: Aceh Nutrition Journal, 2026)
Cholesterol levels are vital indicators of the risk of metabolic disease. However, data on specific lifestyle determinants contributing to hypercholesterolemia within the Chronic Disease Management Program (Prolanis) population remain limited, despite their enrollment in routine monitoring programs. This study aimed to analyze the association between cholesterol intake, fiber intake, and physical activity with cholesterol levels in Prolanis participants.  This cross-sectional study involved 42 Prolanis participants aged 42–76 years at the Kedato Community Health Center in Bandar Lampung. Nutrient intake was measured using the Semi-Quantitative Food Frequency Questionnaire (SQ-FFQ), physical activity was assessed using the Physical Activity Level (PAL) assessment, and cholesterol levels were measured enzymatically.  Bivariate analysis indicated significant associations between cholesterol intake (OR=11.000; 95%CI: 2.366–51.141), fiber intake (OR=5.600; 95%CI: 1.218–25.751), and physical activity (OR=4.750; 95%CI: 1.226–18.406) with cholesterol levels. BMI and central obesity were not significantly associated with each other. However, in the multivariate logistic regression model, physical activity emerged as the sole independent correlate (Adjusted OR 4.848; 95% CI: 1.026–22.909), whereas the associations for dietary variables were attenuated and lost statistical significance.  Although dietary factors showed initial associations, physical activity was identified as the most robust independent correlate of cholesterol levels among the Prolanis participants in this study. These findings suggest that emphasizing physical activity is a critical component of strategies to address hypercholesterolemia in this population